2008
DOI: 10.1371/journal.pgen.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Genetic Method for Establishing Drosophila Cell Lines Unlocks the Potential to Create Lines of Specific Genotypes

Abstract: Analysis of cells in culture has made substantial contributions to biological research. The versatility and scale of in vitro manipulation and new applications such as high-throughput gene silencing screens ensure the continued importance of cell-culture studies. In comparison to mammalian systems, Drosophila cell culture is underdeveloped, primarily because there is no general genetic method for deriving new cell lines. Here we found expression of the conserved oncogene RasV12 (a constitutively activated form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 52 publications
6
87
0
Order By: Relevance
“…To study the effects of pervasive H3K27 methylation, we used cultured cell lines carrying homozygous mutations in PcG genes, created by the procedure of Simcox et al (2008) (see Methods). Line EZ2-2 is homozygous for E(z)…”
Section: Loss Of Prc2 Functionmentioning
confidence: 99%
“…To study the effects of pervasive H3K27 methylation, we used cultured cell lines carrying homozygous mutations in PcG genes, created by the procedure of Simcox et al (2008) (see Methods). Line EZ2-2 is homozygous for E(z)…”
Section: Loss Of Prc2 Functionmentioning
confidence: 99%
“…In this context, one should also note that Hippo mutant cells from dissected developing wings or eyes do not display obvious cell cycle phasing defects [26,55], suggesting that Hippo might not have a role in mitosis in every cell type. However, RasV12 immortalised cells derived from warts null fly embryos display polyploidy, which suggests a defective tetraploidy checkpoint [61]. Given all these indications, future research is warranted to address how Hippo/Lats (and possibly also Trc) signalling plays a role in mitosis.…”
Section: Hippo Signalling In G2/m In Drosophila Melanogastermentioning
confidence: 99%
“…We therefore established primary cell cultures from embryos with Ras activation (DequĂ©ant et al 2015), SWH pathway inactivation, Wts-RNAi, or the combined alterations (Simcox et al 2008). These lines could be grown continuously in culture for >100 passages, and, upon transplantation in vivo, Ras V12 and Wts-RNAi; Ras V12 formed tumors in flies (Wts-RNAi alone was not tested) (Simcox et al 2008; data not shown).…”
Section: Manipulation Of Ras and Swh Signaling Is Required To Maintaimentioning
confidence: 99%
“…Fly strains rs,hsFLP,y,w 1118 ;Act5C>CD2>GAL4,UAS-RFP/TM3Sb, UAS-NLS-GFP, UAS-Ras V12 (a gift from G. Rubin), UAS-Wts-RNAi (Simcox et al 2008), and UAS-Wts-RNAi;UAS-Ras V12 stocks were used in this study.…”
Section: Cell Linesmentioning
confidence: 99%